2006
DOI: 10.22198/rys.2006.36.a583
|View full text |Cite
|
Sign up to set email alerts
|

El impacto de la iniciativa de inocuidad alimentaria de Estados Unidos en las exportaciones de hortalizas frescas del noroeste de México

Abstract: La iniciativa de inocuidad alimentaria del gobierno de Estados Unidos surge como respuesta a un problema de salud pública, y la búsqueda de solución origina una serie de reglamentaciones, que pueden convertirse en una barrera técnica al comercio (BTC), sobre todo para exportaciones de hortalizas frescas de países como México, que no cuentan con la tecnología y los recursos necesarios para adaptarse a los nuevos requerimientos. Se presume que la iniciativa afectará negativamente a México por dos razones: la con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
2
0
2
Order By: Relevance
“…Costs to become certified can be prohibitive to a small entrepreneur, producer, or middleman [62]. Avendaño and Varela [30] and Avendaño et al [63] found that the certification process increased the total costs by 2 to 10% for big exporters of fresh vegetable in Northwestern Mexico. These authors estimated that producers faced a total of $15,000 USD in production costs during the six to 12 months needed to undergo the full certification process.…”
Section: Economic Barriers For Certification Experienced By Producersmentioning
confidence: 99%
“…Costs to become certified can be prohibitive to a small entrepreneur, producer, or middleman [62]. Avendaño and Varela [30] and Avendaño et al [63] found that the certification process increased the total costs by 2 to 10% for big exporters of fresh vegetable in Northwestern Mexico. These authors estimated that producers faced a total of $15,000 USD in production costs during the six to 12 months needed to undergo the full certification process.…”
Section: Economic Barriers For Certification Experienced By Producersmentioning
confidence: 99%
“…Costs to become certificate can be prohibitive to a small entrepreneur, producer, or middleman [48,49]. Avendaño and Varela [14]; Avendaño et al [50] found that the certification process increased the total costs by 2 to 10% for big fresh vegetable exporters in Northwestern Mexico. These authors estimated that producers faced a total of $15,000 USD in production costs during the six to twelve months needed to undergo the full certification process.…”
Section: Certifications In Producersmentioning
confidence: 99%
“…Esta inserción debe garantizar no sólo un acceso más amplio a los mercados externos sino que, al mismo tiempo, logre consolidar su posición en los mercados internos (Rojas et al, 2000). Avendaño et al (2006) los requerimientos de inocuidad en los mercados internacionales se constituyen en barreras técnicas al comercio y disminuyen la competitividad de los exportadores al implicar mayores costos de producción.…”
Section: Figura 1 El Diamante De Porterunclassified